Mobile Health for Adherence to Antiretroviral Therapy in HIV-AIDS: A Systematic Review - Alandia Alandia; Sri Yona (Indonesian Journal of Global Health Research, 2024)
The prevalence of HIV/AIDS presents a significant global health challenge, impacting populations worldwide. Despite advancements in antiretroviral therapy (ART), adherence to medication remains suboptimal, contributing to increased transmission risks. Objective: This study aims to explore the effectiveness and potential of mobile health (mHealth) technologies in enhancing adherence to ART among individuals living with HIV/AIDS. Method: This study conducted a systematic search across major databases including PubMed, Sage Journals, Scopus, SpringerLink, and ProQuest from 2019 to 2024. The inclusion criteria comprised full-text English articles, randomized controlled trials (RCTs), and studies focusing on mHealth interventions among HIV patients. Results: The utilization of mHealth interventions demonstrated a positive impact on improving knowledge, perception, and social support among PLWHA, thereby enhancing medication adherence. Conclusions: Integrating mHealth technologies into healthcare strategies can significantly improve adherence to ART among individuals with HIV/AIDS. Healthcare providers should embrace these innovations to optimize patient care outcomes and address global HIV/AIDS challenges effectively